The Deaf in Iceland : mental health and attitudes towards psychological services - Sólveig Eyfeld Unnardóttir 1983- (2018)
Background: Issues of the Deaf in Iceland have not been in the mainstream discussion in recent years. Knowledge about mental health and use of psychological services among the Deaf in Iceland is lacking. The Deaf face many hindrances when seeking service in general, for example difficulties with communication and access to interpreter services. Few studies abroad show that deaf individuals prefer not to have an interpreter with them to psychological appointment. Aims: In the present study the main goals were: (1) How often have Icelandic deaf individuals used psychological services, (2) Are there differences between age groups regarding the amount of usage of psychological services, (3) How accessible are psychological services for individuals who are deaf, (4) What form of mental health services would be suitable to serve the best interest of the deaf, and (5) What is the mental health status of the Deaf in Iceland compared to the general population in Iceland? Method: Total 61 individuals that were deaf answered an electronic questionnaire via e–mail. All members of the Association of the Deaf in Iceland in the ages 18 and up were invited to participate in the study. Descriptive statistics and chi–square test of independence was used to study prevalence and group differences in prevalence of mental health problems and use of and attitudes towards psychological services. The Deaf sample was compared to data from study of The Directorate of Health from the year 2012. Results: Participants younger than 50 years old were more likely to have been to psychological appointment than the older group (86.4% to 59.3%). Majority of participants in both age groups rated their access to psychological services as good or very good. More than half of the participants in the younger group rated quality of the services as bad or very bad. Both age groups preferred a private appointment with psychologist that knows sign language and has good knowledge of Deaf culture. The Deaf sample showed more depressive and stress symptoms ...